Analisa Kestabilan Lereng Studi Kasus Kelongsoran Ruas Jalan Mandeh-Sungai Nyalo Kecamatan Koto Xl Tarusan, Kabupaten Pesisir Selatan - Sahmijar Sahmijar; Bambang Heriyadi (Departemen Teknik Pertambangan FT UNP, 2019)
Abstract. To design safe slope, using Bishop Method and it helped Geostudio application. physical properties parameter (weight of content, specific gravity, the water level) and mechanics (cohesion and shear angle). The analysis of safe slope was based on the value of safety factor, based on Bowles the value of safety factor >1,25. There were 2 layers in the slope, in the first layer the value of shear angle 21,80 showed clay soil and in the second layer the value of shear angle 31,660 showed sandy clay soil. The result of safety factor using Geostudio application in the condition of natural soil was gotten the value of safety factor 1,388 showed that safe slope and in the saturated condition was gotten safety factor 1,046 it meaned the slope was in critical condition. Recommendation of safe slope design used decreasing sideways slope method, it consist of 4 bench. In the top bench the height was 5m and the sideways a was 45° and it was gotten safety factor =1,692 , in the second bench the height was 4m and the sidewayas was 45° and it was gotten safety factor = 1,333, in the third bench the height was 5 m and the sideways was 45° and it was gotten safety factor =1,294 , and in the last bench the height was 5m and the sideways was 45°, the result of overall was gotten safety factor = 1,288, based on Bowles (2000) the safety factor was safeKeywords: Bishop method, geostudio, water level, cohesion, safety factor